Deletion of ubiquitin fold modifier protein Ufm1 processing peptidase Ufsp in L. donovani abolishes Ufm1 processing and alters pathogenesis. - Sreenivas Gannavaram; Sonya Davey; Ines Lakhal-Naouar; Robert Duncan; Hira L Nakhasi (Public Library of Science (PLoS), 2014)
Previously, we showed Leishmania donovani Ufm1 has a Gly residue conserved at the C-terminal region with a unique 17 amino acid residue extension that must be processed prior to conjugation to target proteins. In this report, we describe for the first time the isolation and characterization of the Leishmania Ufm1-specific protease Ufsp. Biochemical analysis of L. donovani Ufsp showed that this protein possesses the Ufm1 processing activity using sensitive FRET based activity probes. The Ufm1 cleavage activity was absent in a mutant Ufsp in which the active site cysteine is altered to a serine. To examine the effects of abolition of Ufm1 processing activity, we generated a L. donovani null mutant of Ufsp (LdUfsp(-/-)). Ufm1 processing activity was abolished in LdUfsp(-/-) mutant, and the processing defect was reversed by re-expression of wild type but not the cys>ser mutant in the LdUfsp(-/-) parasites. Further LdUfsp(-/-) mutants showed reduced survival as amastigotes in infected human macrophages but not as promastigotes. This growth defect in the amastigotes was reversed by re-expression of wild type but not the cys>ser mutant in the Ufsp(-/-) indicating the essential nature of this protease for Leishmania pathogenesis. Further, mouse infection experiments showed deletion of Ufsp results in reduced virulence of the parasites. Additionally, Ufsp activity was inhibited by an anti-leishmanial drug Amphotericin B. These studies provide an opportunity to test LdUfsp(-/-) parasites as drug and vaccine targets.